Improvement of Populus deltoides Bartr. Ex Marsh. In India - II. Future Strategy - Singh, N. B.; Kumar, Dinesh; Rawat, G. S.; Shrivastava, Shivendu K. (Indian Forester, 1999)
A coordinated, multi-organisational strategy for research, development and dissemination of improved clones of P. deltoides has been developed and discussed in this paper. The programme has been initiated by research groups of various research institutes, universities and Uttar Pradesh State Forest Department under the technical guidance and coordination of the Chief Technical Advisor (CTA) and Associate CTA for Poplar. The programme envisages carrying out of multilocation clonal trials of promising clones identified to be existing in the country. A breeding programme for control pollination ofthe promising clones using 4 Ã— 4 assortative mating design has also been launched. Seed from 104 candidate plus trees of P. deltoides from 44 wild stands in 11 States of South-eastern USA has been obtained in pursuit of this strategy. Clones will be developed at FRI from the seeds of control pollination and introduction from the U.S.A. These clones will also be tested at multiple sites under the All-India Coordinated Poplar Improvement Programme. A 10-year action for FRI and all other coordinating research units has also been prepared.